An Algorithm for the Noninvasive and Personalized Measurement of Microvascular Blood Viscosity Using Physiological Parameters. (1st September 2020) - Sun, Ge; Yang, Lin; Wang, Weiwei; Zhang, Song; Luo, Zhichang; Wu, Guanghui; Liu, Xiaohong; Hao, Dongmei; Yang, Yimin; Li, Xuwen
Abstract : Blood viscosity is one of the important parameters to characterize hemorheological properties of the human body. Its real-time and dynamic measurement has important physiological significance for studying the development and prevention of chronic diseases. This study researched noninvasive and personalized measurement of microvascular blood viscosity. In the microcirculation capillary network blood flow model, combined with pulse wave parameters, multiple regression analysis was used to fit the simulated radius of personalized physiological blood vessels to calculate the microvascular blood viscosity. The fitted value related to the simulated radius of the physiological blood vessel had a high correlation with the corresponding theoretically derived value (correlation coefficient: 0.904, P ≤ 0.001 ). The calculated value of the microvascular blood viscosity had a certain correlation with the clinical whole blood viscosity at a low shear rate (correlation coefficient: 0.443, P < 0.05 ). This algorithm could provide effective means for noninvasive and long-term individual monitoring and family health care.